Role Of Bricolage In Women Green Entrepreneurship: An Exploratory Study - Potluri, Seema (Curtin University, 2024)
The study is regarding ‘Women Green entrepreneurship’ (WGE), that implies participation of women in green entrepreneurship, a proposition aiming at contributing to environmental improvement as well as women empowerment. The thesis, that has been developed in the context of India and Australia, focusses on validating and conceptualizing WGE, identification of challenges and enablers of WGE, and the unique strategies and behaviors that current women green entrepreneurs employ to overcome those challenges.